2021
DOI: 10.1063/5.0076427
|View full text |Cite|
|
Sign up to set email alerts
|

Data-driven splashing threshold model for drop impact on dry smooth surfaces

Abstract: We propose a data-driven threshold model to redefine the boundary between deposition and splashing for drop impact on dry smooth surfaces. The starting point is the collection and digitization of multiple experimental sources with varying impact conditions. The model is based on the theory of Riboux and Gordillo [Riboux and Gordillo, “Experiments of drops impacting a smooth solid surface: A model of the critical impact speed for drop splashing,” Phys. Rev. Lett. 113, 024507 (2014)] and is obtained by an uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The Gordillo-Riboux model has since been expanded by Pierzyna et al using a data-driven threshold model which re-defines the threshold for droplet splashing on a dry smooth surface by collating a large number of experimental sources with different conditions and analysing the data with an uncertainty qualification analysis combined with machine learning [31]. The Gordillo-Riboux model can be considered as the special case where the parameter β for determining splashing is a constant (in the general case, each impact parameter has a different dependence on β).…”
Section: Introductionmentioning
confidence: 99%
“…The Gordillo-Riboux model has since been expanded by Pierzyna et al using a data-driven threshold model which re-defines the threshold for droplet splashing on a dry smooth surface by collating a large number of experimental sources with different conditions and analysing the data with an uncertainty qualification analysis combined with machine learning [31]. The Gordillo-Riboux model can be considered as the special case where the parameter β for determining splashing is a constant (in the general case, each impact parameter has a different dependence on β).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the increasing availability and accessibility of data, data-driven approaches-and machine learning in particular-have attracted increasing attention among fluid researchers as a faster and cheaper alternative or complement to experimental and numerical studies [32][33][34][35][36][37][38][39]. Regarding drop impacts, several machine-learning-based studies have been carried out [40][41][42][43]. Notably, a number of studies on predicting the maximum spreading factor of a non-splashing drop under various conditions were published in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The examples include rain drops falling on insect wings, splashing of pesticide on plant leaves, coffee stain, food industry and inkjet printing. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Physics of droplet-substrate interaction has been an attractive field of science in various technologies including healthcare, aerospace, electronics, coatings, printings and materials science. Previous studies about droplet impact on rigid substrates demonstrated following physical events: deposit (adhesion), breakup (fragmentation), prompt splash, corona splash, partial bounce and complete bounce as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The examples include rain drops falling on insect wings, splashing of pesticide on plant leaves, coffee stain, food industry and inkjet printing. 119 Physics of droplet-substrate interaction has been an attractive field of science in various technologies including healthcare, aerospace, electronics, coatings, printings and materials science. 20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation